2018
DOI: 10.1007/s11130-018-0673-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Rich Potato Improves Arterial Stiffness in Healthy Adults

Abstract: Arterial stiffness is an emerging risk factor for cardiovascular disease and dietary anthocyanins may be important in mediating vascular tone. The present study investigated the effect of consumption of an anthocyanin-rich potato, Purple Majesty on arterial stiffness measured as pulse wave velocity in 14 healthy male and female adults. Participants consumed 200 g/day of cooked purple potato containing 288 mg anthocyanins, or a white potato containing negligible anthocyanins for 14 days, separated by a 7-day wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…Fruits are not the only food rich in polyphenols that have shown beneficial effects. For example, 200 g of purple majesty potatoes, containing 288 mg of anthocyanins, decreased pulse wave velocity, a measure of arterial stiffness, in both healthy males and females consuming 200 g of potatoes a day for 14 days [73]. Since arterial stiffness is an independent indicator of CVD, purple majesty potatoes consumption would be beneficial against these diseases.…”
Section: Polyphenols In Human Healthmentioning
confidence: 99%
“…Fruits are not the only food rich in polyphenols that have shown beneficial effects. For example, 200 g of purple majesty potatoes, containing 288 mg of anthocyanins, decreased pulse wave velocity, a measure of arterial stiffness, in both healthy males and females consuming 200 g of potatoes a day for 14 days [73]. Since arterial stiffness is an independent indicator of CVD, purple majesty potatoes consumption would be beneficial against these diseases.…”
Section: Polyphenols In Human Healthmentioning
confidence: 99%
“…Arterial stiffness is an independent risk factor for the development of CVD [ 100 ]. Tsang et al explored the effects of an anthocyanin-rich potato, Purple Majesty (PM), on pulse wave velocity (PWV), a clinical measure of arterial stiffness [ 101 ]. They found that consumption of 200 g/day of PM potatoes, for 14 days, significantly reduced carotid-femoral PWV, in healthy individuals, whereas consumption of an equivalent amount of white potato had no effect.…”
Section: Relationship Between Potato Consumption and Non-communicamentioning
confidence: 99%
“…In the present study, we did not detect any difference in PWV, probably because we included relatively healthy participants and the study was of short duration. However, a 14-d study where 200 g/d of Purple Majesty potatoes was consumed showed a small, but significant change in PWV (-0•3 m/s, P = 0•001) (10) . No changes in SBP or diastolic BP were observed in that study, and the authors attributed the reduction in PWV to the antioxidants in the purple potatoes.…”
Section: Discussionmentioning
confidence: 89%
“…The few randomised, controlled trials that have been conducted have not found adverse cardiometabolic changes with potato consumption (8)(9)(10) . However, these studies examined potatoes with a high phenolic load that is not representative of potatoes typically consumed by Americans, lacked a comparator condition that reflects real-world dietary substitutions and included relatively small sample sizes.…”
mentioning
confidence: 99%